PENGARUH METODE PENYULUHAN SECARA DIRECT COMMUNICATION MELALUI KUNJUNGAN LAPANGAN TERHADAP TINGKAT PENGETAHUAN PETANI DALAM PENCEGAHAN GEJALA PENYAKIT ANTRAKNOSA PADA CABAI RAWIT DI KECAMATAN SAMBELIA KABUPATEN LOMBOK TIMUR: The Effect of Direct Communication Extension Methods Through Field Visits on the Level of Farmers Knowledge in Preventing Anthracnose Disease Symptoms in Chili Peppers in Sambelia District, East Lombok Regency - Asasandi, I Gusti Ngurah Aryawan; Masani, Sab’ul (Ganec Swara, 2026)
The purpose of this study was to determine the effect of the use of direct communication extension methods through field visits on the level of farmer knowledge in preventing anthracnose disease symptoms in cayenne peppers in the Sambelia District. This study used a simple linear regression analysis, which aimed to determine the relationship between the independent variables, namely, the agricultural extension method and the field visit method, which together affected the dependent variable, namely, the level of farmer knowledge on preventing anthracnose disease in cayenne peppers. The number of respondents was 40. The results of the study found that (1) the extension method through the concept of direct communication by conducting field visits influenced farmer knowledge in understanding the prevention of anthracnose disease in cayenne pepper plants. (2) The equation model showed that the regression coefficient of farmer knowledge was 0.667, indicating that every 1 unit increase in the independent variable, namely extension using the field visit method, would increase by 0.667 units.